2020
DOI: 10.1590/0104-530x3800-20
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain risk management and risk ranking in the automotive industry

Abstract: Supply chain risk management (SCRM) has a strong influence on the cooperation among partners and the performance of the entire production chain. A supply chain designed to minimize risks enables firms to establish a competitive position and provides long-term benefits to stakeholders. The SCRM system should be structured to manage both routine and extraordinary risks, such as natural disasters and major accidents. The risks should be managed both reactively, by monitoring changes in the chain, the needs of cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 63 publications
(112 reference statements)
0
19
0
2
Order By: Relevance
“…Over the past decade, our knowledge and awareness of supply chain risk management (SCRM) have risen due to technological and market turbulence, volatile customer demand, along with competitive intensity [30]. A definition of supply chain risk is "the variation in the distribution of possible supply chain outcomes, their likelihoods, and their subjective values" [31].…”
Section: Supply Chain Risk Managementmentioning
confidence: 99%
“…Over the past decade, our knowledge and awareness of supply chain risk management (SCRM) have risen due to technological and market turbulence, volatile customer demand, along with competitive intensity [30]. A definition of supply chain risk is "the variation in the distribution of possible supply chain outcomes, their likelihoods, and their subjective values" [31].…”
Section: Supply Chain Risk Managementmentioning
confidence: 99%
“…The development of new technologies, such as 5th generation mobile networks, challenges the technical development of NEV. Accordingly, the potential for technological innovation is a safeguard to continuously advance the safety level, efficiency, and quality of the supply chain [22,23,28].…”
Section: Non-conforming Technical Level and Development Potential (E23)mentioning
confidence: 99%
“…The logistics distribution risks between diverse nodes mainly predicate the interruption caused by the choice of transportation methods, the arrangement of transportation batches and quantities, third-party logistics service providers, and other unexpected factors [23,34]. An unreasonable design of the logistics distribution network may initiate delays in delivery, which, in turn, will cause out-of-stock losses, and thus, would bring a poor consumer experience to consumers, adversely exerting a bad influence on car brands.…”
Section: Logistics Distribution Risk (E25)mentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the risks perceived from the second tier are higher than those of the first-tier suppliers in the chain. Dias, Hernandez, and Oliveira [24] determined the risk factors for the automobile sector through a survey and then applied the Analytic Hierarchy Process (AHP) to rank the risks. The developed instrument provides a platform to assess the risk score for automobile companies.…”
Section: Literature Review 21 Global Supply Chainmentioning
confidence: 99%